Impact of Compositional Engineering on PTB7-Th:PC71BM Capacitive Humidity Sensor Performance - Fatima, Noshin; Lim, Lih Wei; Bukhari, Sarah; Raza, Ehsan; Aziz, Fakhra; Shah, Zarbad; Sulaiman, Khaulah (Springer, 2024)
The current investigation focuses on the development of capacitive humidity sensors utilizing an organic polymer blend of poly[4,8-bis(5-(2-ethylhexyl)thiophene-2-yl)benzo[1,2-b;4,5-b ']dithiophene-2,6-diyl-alt-(4-(2-ethylhexyl)-3-fluorothieno[3,4-b]thiophene-)-2-carboxylate-2-6-diyl)] (PTB7-Th) and [6,6]-phenyl-C71-butyric-acid methyl ester (PC71BM), which were successfully achieved. A cost-effective spin-coating technique was employed to produce surface-type sensors in the Al/PTB7-Th:PC71BM/Al horizontal geometry. The investigation focuses on the capacitive behavior of the devices under ambient conditions, specifically at room temperature. The devices are subjected to an alternating current operational bias of 1 V, while the relative humidity (RH) is varied within the range of 20-95%. The sensors are examined at frequencies of 100 Hz, 1 kHz, 10 kHz, and 100 kHz. Specifically, the sensors demonstrate improved sensitivity to changes in capacitance in relation to relative humidity when operating at a frequency of 100 Hz. In addition, an optimal volumetric ratio of 1.5:1 is selected for PTB7-Th to PC71BM. The optimized composite sensor demonstrates superior performance, exhibiting minimal hysteresis of 6.16% and significant sensitivity of 1.58 pF/% RH. In addition, response and recovery times of 2 s and 3 s, respectively, are obtained. The results of investigations demonstrate that the composite sensor exhibits significant improvements in sensing parameters compared to single-material sensors. As a result, the composite sensor has great potential for use in advanced sensor applications, especially in the education sector in underdeveloped countries.
Keywords: Capacitance; humidity sensor; organic semiconductor; polymer composite; surface-type